Characterization of Early and Late Adopters of ATM Card in Indian Banking Industry - Kaur, Kamalpreet (The South East Asian Journal of Management, 2012)
The present study deals with affect of adoption pattern of the ATMs by banks on its characteristics. With the exploration of various characteristics of the banks like Size, Profi tability, Efficiency, Cost of Operations, Asset quality and Credit risk, Financing Pattern, Diversifi cation and Age etc.; the study has tried to differentiate between the early and late adopter category of the banks regarding ATM cards. The banks have been categorized into early and late adopters on the basis of their adoption period. For this purpose, 50 scheduled commercial banks consisting of 27 Public Sector Banks and 23 Private Sector Banks have been taken as sample to investigate the various aspects of and early adopter banks in comparison to late adopter banks. The time period of the study is 20 years i.e. from 1991 to 2010. It can be concluded that the initiators and fi rst movers take advantage over the late adopters and laggards. They have found to perform better in terms of various parameters. Overall, the early adopter banks are larger in size, more diversifi ed, having lesser branches, more market share and wide ATM network as compared to late adopter ones. Thus, the empirical results evidently reveal that the both the groups have their own different characteristics.